Disturbed gut microbiota explains persistent abdominal pain after a major environmental disaster - Yusof, Nurfadhilah (2017)
Background: It is unknown if there is association between abdominal pain and poor water, sanitation and hygiene (WaSH) practices and if small intestinal bacterial overgrowth (SIBO) and/or gut dysbiosis explains abdominal pain after a major flood. Methods: Abdominal symptoms, quality of life, psychological disturbances, WaSH practices, SIBO and stools for high-throughput sequencing were assessed in flood victims. Results: Of 211 participants (mean age 54.5 years, females 71%), 37.9% had abdominal pain. Poor WaSH practices during flood and irritable bowel syndrome (IBS) were associated with abdominal pain (both P < 0.04). Those with abdominal pain experienced worse quality of life and more anxiety (both P < 0.05). SIBO was associated with abdominal pain (P = 0.01), poor water practices during flood (P = 0.04) and limited physical functioning (P = 0.02). Using linear discriminant analysis effect size method, gut dysbiosis was observed in those with anxiety (Bacteroidetes and Proteobacteria, effect size 4.8), abdominal pain (Fusobacteria, Staphylococcus, Megamonas and Plesiomonas, effect size 4.0) and IBS (Plesiomonas and Trabulsiella, effect size 3.0). Conclusions: Disturbed gut microbiota because of environmentally-derived organisms may explain persistent abdominal pain after a major environmental disaster in the presence of poor WaSH practices.